Impact of COVID-19 pandemic on hotel service quality and customer satisfaction / Laili Afliza Azis and Nur Hidayah Che Ahmat - Azis, Laili Afliza; Che Ahmat, Nur Hidayah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The hotel industry is one of the hardest-hit industries by the COVID-19 pandemic. Since the outbreak started in December 2019, there have been massive cancellations of hotel reservations due to the global travel restrictions, resulting in billions of dollars in revenue losses. In Malaysia, various government restriction orders and preventative measures have negatively impacted the hotel industry. The new standard operating procedures have affected how employees serve their customers, thus influencing customer experience staying at the hotel during the pandemic. Therefore, this study examined the impact of the COVID-19 pandemic on hotel service quality and customer satisfaction. An online survey was developed and distributed to social media platforms targeted to all customers staying at hotels in Pulau Pinang during the COVID-19 pandemic. Considering the population size in Malaysia, this study expected to sample 384 participants; however, only 160 responses were used in the analysis (42% response rate). The remaining responses were removed due to ineligibility. According to the findings, safety and security, customer interaction, and waiting time significantly influenced customer satisfaction. Additionally, waiting time was the most influential factor influencing hotel service quality and customer satisfaction. The new normal of doing business has changed the way hoteliers deliver their products and services to their customers, influencing overall customer satisfaction. Findings could assist hotel operators, and employees improve their quality of service during and in the post-pandemic. Limitations and future research recommendations are presented.